How the Management of Children With Congenital Central Hypoventilation Syndrome Has Changed Over Time: Two Decades of Experience From an Italian Center - Porcaro, Federica; Paglietti, Maria Giovanna; Cherchi, Claudio; Schiavino, Alessandra; Chiarini Testa, Maria Beatrice; Cutrera, Renato (Frontiers in Pediatrics, 2021)
Background: Congenital central hypoventilation syndrome (CCHS) is a rare disorder whose clinical phenotype is closely related to genotype. Methods: A retrospective analysis has been conducted on 22 patients with CCHS, who were referred to the Pediatric Pulmonology and Respiratory Intermediate Care Unit of Bambino Gesù Children's Hospital (Italy) for a multidisciplinary follow-up program between 2000 and 2020. Results: Apnea and cyanosis were the most frequent symptoms at onset (91%). Overall, 59% of patients required tracheostomy and invasive mechanical ventilation (IMV) in the first months of life. Thirty-two percent of patients had Hirschsprung disease (HSCR) that was associated with longer polyalanine repetitions or non-polyalanine repeat expansion mutations (NPARMs). Polyalanine repeat expansion mutations (PARMs) were more frequent and two novel NPARMs (c.780dupT and C.225–256delCT) were described in 14% of patients. Focal epilepsy was first described in 14% of patients and neurocognitive and neuromotor impairment involved 27% and 23% of children, respectively. Symptoms due to autonomic nervous system dysfunction/dysregulation (ANSD)—including strabismus (27%), dysphagia (27%), abnormal heart rhythm (10%), breath-holding spells (9%), and recurrent seizures due to hypoglycemia (9%)—were associated with an increased number of polyalanine repetitions of exon 3 or NPARMs of PHOX2B gene. Overall, the number of patients with moderate to severe phenotype initially treated with non-invasive ventilation (NIV) increased over time, and the decannulation program was concluded with 3 patients who started with IMV. Conclusions: Our study confirms that more severe phenotypes of CCHS are related to the number of polyalanine repetitions or to NPARMs. Although invasive ventilation is often required by patients with severe genotype/phenotype, gradual acquisition of specific skills in the management of patients with CCHS and technological improvements in mechanical ventilation allowed us to improve our therapeutic approach in this population.